Patterns and Outcomes of Illnesses in Medical Patients Admitted to Holy Family Hospital in a period of Three Months - Fariha Idrees , Hamna Atique , Mujtaba Haider , Muhammed Khurram , Fariha Idrees , Hamna Atique , Mujtaba Haider , Muhammed Khurram (Journal of Rawalpindi Medical College, 2021)
Background: Health policy makers often use data describing prevalence, morbidity and mortality to assess the burden, requirements of resources and quality of the health service. The aim of this study is to recognize the patterns and treatment outcomes of diseases in a medicine unit of Holy Family Hospital, Rawalpindi. Objective: To assess the pattern and treatment outcomes of illnesses presenting in a medicine department of Holy Family Hospital, Rawalpindi in period of three months. Materials and Methods: This descriptive cross-sectional study was undertaken from 1st March to 31st May of 2019, when all the patients admitted in Medical Unit were approached for consent to participate in the study. Data were collected using a self-administered questionnaire-based interview of respondents. Data were analyzed by using Statistical Package for Social Sciences Version 23. Results: A total of 579 participants were enrolled into the study, out of which 374 (64.6%) were male and 205 (35.4%) were female with mean age 52.23. Majority of participants were admitted via emergency (92.23%). The most prevalent illnesses were chronic renal disease, asthma, decompensated chronic liver disease and stroke; with hypertension being the commonest co-morbid condition (6.2%). Of those admitted to the facility, 53.5% patients after treatment according to advice and 22.5% left the hospital against medical advice. Mortality rate was 23.8%. Conclusion: Patients with a wide variety of diseases were admitted to the medical unit mainly through emergency.1 in 5 patients admitted in acute medical unit suffered mortality.